2013
DOI: 10.1089/ham.2012.1080
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Ginkgolide B on High Altitude Cerebral Edema of Rats

Abstract: Ginkgolide B (GB) is one of the ginkgolides isolated from leaves of the Ginkgo biloba tree. The aim of this study was to investigate whether GB has a protective effect on high altitude cerebral edema (HACE) of rats. HACE was induced by hypobaric hypoxia exposure for 24 hours in an animal decompression chamber with the chamber pressure of 267 mmHg to simulate an altitude of 8000 m. Before the exposure, three doses (3, 6, and 12 mg·kg(-1)) of GB were given intraperitoneally (ip) daily for 3 days. Effects of GB o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In another study conducted in WAG/Rij rats, it was determined that 1%, 10%, and 30% DMSO injections had no effect on absence seizures in all recording periods (Kovács et al, 2011). The doses and the routes of administration of the active components of EGb 761 have been determined according to the literature (Botao et al, 2013; Huang et al, 2012; Shah et al, 2011). These chemicals were injected intracerebroventricularly (i.c.v.)…”
Section: Methodsmentioning
confidence: 99%
“…In another study conducted in WAG/Rij rats, it was determined that 1%, 10%, and 30% DMSO injections had no effect on absence seizures in all recording periods (Kovács et al, 2011). The doses and the routes of administration of the active components of EGb 761 have been determined according to the literature (Botao et al, 2013; Huang et al, 2012; Shah et al, 2011). These chemicals were injected intracerebroventricularly (i.c.v.)…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, in recent years, there has been increasing attention to anti-inflammatory and antioxidant substances derived from a number of natural substances, especially traditional Chinese herbal medicines. Natural antioxidants such as ginkgolide B, 121 quercetin, 62 tetrahydrocurcumin, 100 areca polyphenols, 68 salidroside, 97 , 122 phenylethanol glycoside 99 and potentilla anserine L. polysaccharide 101 can reduce oxidative stress and inflammation in a hypobaric and hypoxic environment by enhancing the activity of antioxidant enzymes and inhibiting NF-κB inflammatory signaling, so as to prevent or treat HACE. In addition, endogenous Exendin-4 and ganglioside GM1 are also thought to alleviate HACE by inhibiting inflammation and oxidative stress ( Table 2 ).…”
Section: Study On Redox Homeostasis In the Treatment Of Hacementioning
confidence: 99%
“…The protective effect of GB may be related to its antioxidation and inhibition of caspase-dependent apoptosis pathway. [ 60 , 121 ] Ex-4 Isolated from the saliva secretion of the Gila monitor lizard Heloderma suspectum Polypeptide (enteric insulin-stimulating mimic peptide of 39 amino acids) (1) Ex-4 preconditioning can effectively inhibit inflammation and oxidative stress and alleviate brain injury by reducing the expression of IL-6, TNF-α and NF-κB in HACE model rats; (2) Ex-4 can increase the expression of VEGF and promote angiogenesis to maintain the integrity of blood-brain barrier, reduce brain water content and improve HACE in HACE model rats. [ 95 ] GM1 A ganglioside in the mammalian brain, found chiefly in neurons.…”
Section: Study On Redox Homeostasis In the Treatment Of Hacementioning
confidence: 99%
“…Administration of GB 2 h after reperfusion effectively decreased infarction volume and brain edema in rats with MCAO (Fang et al 2010). Botao et al (2013) found that GB pretreatment reduced brain water content, increased superoxide dismutase activity and glutathione concentration, decreased MDA concentration, and decreased active caspase-3 and PARP expression in rats with high altitude cerebral edemas. GK, a derivate of GB, given at a higher dose also attenuated cerebral infarction and repressed brain edema formation in MCAO rats (Ma et al 2012).…”
Section: Mechanisms Of Ginkgolides and Bilobalide In Neuron Protectiomentioning
confidence: 99%